2017
DOI: 10.1001/jamaneurol.2016.4439
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Nonlesional Neocortical Epilepsy

Abstract: IMPORTANCEThe proportion of surgery for nonlesional neocortical epilepsy has recently increased, with a decrease in surgery for mesial temporal lobe epilepsy. However, there are only a few studies regarding the long-term surgical outcome and the potential prognostic factors for patients with nonlesional neocortical epilepsy.OBJECTIVE To evaluate the long-term surgical outcome and to identify possible prognostic factors in patients with nonlesional neocortical epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
4
26
1
2
Order By: Relevance
“…Complete resection of epileptogenic zones has been identified as one of the most important predictors of postoperative seizure outcomes in patients with extratemporal lobe epilepsy . However, we found no association between the completeness of resection and seizure outcomes.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Complete resection of epileptogenic zones has been identified as one of the most important predictors of postoperative seizure outcomes in patients with extratemporal lobe epilepsy . However, we found no association between the completeness of resection and seizure outcomes.…”
Section: Discussioncontrasting
confidence: 87%
“…In previous studies, changes in the postoperative seizure status were observed in >30% of patients with temporal lobe epilepsy, whereas only 10% of patients with extratemporal lobe epilepsy experienced changes in their postoperative seizure status during followup. 18,19 In the present study, changes in the postoperative seizure status were also observed in 15.4% of patients. However, the total seizure-free rate was stable for 5 years after surgery (the difference in the seizure-free rate between 3 months and 5 years after surgery was not statistically significant).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A study of temporal excision using survival analysis found that those with normal or ‘other’ pathology, as judged by a combination of histopathology and MRI findings, had a worse outcome than those with HS or foreign tissue lesions 13. A recent study of 109 people with unremarkable MRI found 54% to be seizure free 1-year postsurgically 14. Caveats with the interpretation of this study are that a more liberal definition of seizure freedom was used (Engel group 1) than in our studies and pathologies such as focal cortical dysplasia and dysembryoplastic neuroepithelial tumour would be expected to be detected by contemporary MRI.…”
Section: Discussionmentioning
confidence: 99%